THE PRE-OROGENIC VOLCANO-SEDIMENTARY COVERS OF THE WESTERN TETHYS OCEANIC BASIN: A REVIEW - Principi, Gianfranco; Bortolotti, Valerio; Chiari, Marco; Cortesogno, Luciano; Gaggero, Laura; Marcucci, Marta; Saccani, Emilio; Treves, Benedetta (Ofioliti, 2004)
The records of the Jurassic Western Tethys Ocean are the ophiolitic rocks now scattered in the Tertiary orogenic belts of the Alps, Apennines and Betic Cordillera.These ophiolites, involved in a convergent margin environment, are affected I) by HP/LT metamorphism derived from a subduction process or II) by very low grade overprint, corresponding to the tectonic prism at the margin of the overriding plate. On the whole, they share common characteristics:a- The MORB geochemical signature.b- The ophiolitic successions often “reduced” and thin.c- The volcano-sedimentary covers often directly overlying the serpentinised peridotites.d- The widespread occurrence of cherts as Jurassic pelagic sediment.In the thickest “complete” ophiolitic successions, basalt flows, generally thin, are preceded and followed by ophiolitic breccias. Only the basal portion of the breccias on top of the serpentinites (Levanto Breccias) has a tectonic origin, all other levels have a sedimentary origin. These breccia-basalt assemblages are overlain by thick sequences of Mt. Alpe Cherts and Calpionella Limestones, followed by Palombini Shales. In the reduced (or incomplete) successions, thin breccias and cherts were directly deposited, above the Levanto Breccias (ophicalcites pro parte), and followed by Palombini Shales.This stratigraphic pattern seems to be widespread in the whole Western Tethys ocean.In some sequences, transitional mid-ocean ridge (T-MOR) basalts are present and the ophiolitic rocks are associated with Variscan continental slices and debris, as in the Err-Platta succession (Central Alps) and in some exotic blocks in the flysch of the External Ligurides (Northern Apennines). In the Balagne (Corsica) T-MOR basalts are associated with quartzarenites. These occurrences show that an unroofed mantle and sections of oceanic crust evolved very near to a continental margin.The different radiolarian ages of the cherts deposited before, within, or on top of the MOR basalts allow to infer a minimum time interval for the Western Tethys oceanisation. This interval can be considered between 16 and 21 Ma (from Late Bajocian to Kimmeridgian/Tithonian). If we assume 1cm/yr spreading rate during this time, the basin would have reached about 150-200 km width. The same ages suggest that the ocean opening was diachronous along the Western Tethys basin.Mainly on the basis of the Northern Apennines and Corsica data, it is possible to reconstruct the following evolutive geodynamic, paleogeographic and sedimentary evolution of the Western Tethys ocean basin:1- Bajocian/Bathonian stage: opening of the Ligurian Northern Apennines oceanic segment and, perhaps, also of the Ligurian, Western and Central Alps ones.2- Bathonian/Callovian stage: opening of all the segments of the Western Tethys ocean basin. The volcano-sedimentary covers formed during these two stages are constituted by breccias, basalts and siliceous pelagites (cherts).3- Tithonian/Berriasian: end of the ocean spreading (Tithonian) and beginning of the quiescent stage in the whole basin, marked by the lack of any tectonic activity and by the sedimentation of the Calpionella Limestones and, locally, of mixed siliceous-calcareous deposits (Nisportino-Murlo Fm.).4- Hauterivian/Santhonian: this is the longest quiescent stage of the basin, dominated by the sedimentation of the Palombini Shales and Limestones. Some siliciclastic deposits are shed from both passive continental margin sides. During the Early Cretaceous, there is also evidence of a rare intraplate magmatism in Southern Tuscany.The Western Tethys ophiolitic successions are similar to those of present day, slow spreading oceans, in particular to those of the Atlantic Ocean (Mutter and Karson, 1992; Tucholke and Linn, 1994). The Galician North Atlantic margin provides a model for the process of mantle denudation. For the oceanic evolution, the model of Tucholke and Linn (1994) is particularly taken in consideration. According to this model, tectonic extension was one major process in the Western Tethys oceanic development.